2000
DOI: 10.1111/j.1651-2227.2000.tb00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of kernicterus in term and near‐term infants in Denmark

Abstract: Classical acute bilirubin encephalopathy (kernicterus) in term and near‐term infants had not been seen in Denmark for at least 20 y until 1994. From 1994 to 1998, however, six cases were diagnosed. Aetiology of the hyperbilirubinaemia was known in two infants; spherocytosis and galactosaemia, most likely known in two infants; possible A‐O blood type immunization, and unknown in two infants. However, one of these last‐mentioned infants had a gestational age of only 36 wk. The maximum plasma total bilirubin conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 19 publications
3
74
2
1
Order By: Relevance
“…Cases of kernicterus continue to be reported worldwide. 4,10,28 Although our study was not designed to assess the incidence of long-term neurologic disease (e.g., kernicterus), a further systematic study estimating the incidence of kernicterus in Canada and its associated morbidity would be valuable. A major limitation of the study was the reliance on self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of kernicterus continue to be reported worldwide. 4,10,28 Although our study was not designed to assess the incidence of long-term neurologic disease (e.g., kernicterus), a further systematic study estimating the incidence of kernicterus in Canada and its associated morbidity would be valuable. A major limitation of the study was the reliance on self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, a recurrence of cases of bilirubin encephalopathy was reported, though recent data suggest that kernicterus never really disappeared [7,8,9,10]. This supposed recurrence, or persistence of bilirubin encephalopathy, is attributed to changing demographics, diminishing clinical experience and increasing nonhospitalized perinatal care.…”
Section: Introductionmentioning
confidence: 98%
“…Although not the aim of this study, we note with great concern that our crudely estimated incidence is high compared with estimates of kernicterus in term infants reported previously. 7,14,39 Our observation warrants additional validation of the kernicterus diagnosis in the Swedish Medical Birth Register and more information on background, clinical course, and outcome in these patients.…”
Section: Figurementioning
confidence: 99%
“…3,4 High levels of unconjugated bilirubin could be associated with brain dysfunction and even permanent brain damage, known as kernicterus. 5,6 In light of the recurrence of kernicterus in healthy term infants, [7][8][9] prediction and early detection of infants at risk have received high priority. Different guidelines and approaches [8][9][10][11][12][13][14][15][16] have been issued, among which that of the American Academy of Pediatrics (AAP) 17 is the most commonly used worldwide.…”
Section: What This Study Addsmentioning
confidence: 99%